Adenoviral Conjunctivitis: A Systematic Review - Mallik, Chinmoy; Abedin, Md Jainal; Hossain, Mohammed Shoaib (IAHS Medical Journal, 2024)
Background: Adenoviral conjunctivitis is an infection of the conjunctive which is the mucous membrane covering the white part of the eye called sclera. Conjunctivitis also refers as pink eye causes conjunctiva inflammation. Adenovirus is responsible for 75% of viral conjunctivitis. Adenoviral conjunctivitis provider infection is still widespread in the US healthcare system and poses a serious risk to patient welfare. Some of the complex of adenoviral conjunctivitis include subepithelial infiltrates, pseudomembrane formation, corneal ulceration and conjunctival scarring. A recent development of the adenoplus assay which is a rapid test to detect adenovirus (Rapid Screening for pathogen Inc. USA) has made it possible to obtain results from samples within 10 minutes. Adenoviral conjunctivitis may produce a pseudomembrane, that is a membrane consisting of inflammatory cells, mucus and dead cells that could stick to the surface of the eye. This systematic review is aimed to design to provide an insight on the clinical characteristics, presentation and treatment about this issue. Methodology: This current study is a systematic review to published studies and articles by using PubMed and Google. Search strategy using appropriate keywords and title. Conclusion: The majority of viral conjunctivitis cases are due to adenoviruses, so effective management of conjunctivitis includes timely diagnosis, appropriate differentiation of the various etiologics and appropriate treatment. IAHS Medical Journal Volume 6(2) December 2023; 87-89